2019
DOI: 10.1007/s12011-018-1578-5
|View full text |Cite
|
Sign up to set email alerts
|

Copper and Zinc Nutritional Issues for Agricultural Animal Production

Abstract: Livestock have presented unique requirements and toxicity issues depending on the species for the various concentrations of Cu and Zn and their interactions with other nutrients especially Fe, Se, Mo, and S. Soil concentrations of these elements and their availability to crops influence the health of the crop and the amount found in vegetative tissues and seeds. Hence, many livestock issues are a result of the soils in the area where production is occurring (Loneragan et al. 1981 ). Whil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
68
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(72 citation statements)
references
References 146 publications
(120 reference statements)
2
68
1
1
Order By: Relevance
“…The required amount of Zn by livestock is about 35 mg Zn kg −1 feed DM (Suttle 2010), although it might depend on the livestock type. Its deficiency can causes numerous disorders in livestock, such as skin parakeratosis, reduced or cessation of growth, general debility, lethargy, and increased susceptibility to infection (Hill and Shannon 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The required amount of Zn by livestock is about 35 mg Zn kg −1 feed DM (Suttle 2010), although it might depend on the livestock type. Its deficiency can causes numerous disorders in livestock, such as skin parakeratosis, reduced or cessation of growth, general debility, lethargy, and increased susceptibility to infection (Hill and Shannon 2019).…”
Section: Introductionmentioning
confidence: 99%
“…99 Zinc's direct impact on the gut microbiota and subsequent host growth has been evaluated in several studies of young livestock animals (piglets, calves, and broiler chickens) that differed in their design (dose levels, measurement time points, etc) and methods. [100][101][102] Most studies have reported small, beneficial effects-suggesting that Zn may shape the intestinal microbiota. However, a consensus is currently lacking.…”
mentioning
confidence: 99%
“…43 Zinc deficiency, as a metabolic factor, has been reported to induce acanthosis and parakeratosis in different species including the horse. 15,22…”
Section: Discussionmentioning
confidence: 99%